Dragon Ball Z. Vol. 16 - Toriyama, Akira, 1955- (Shonen Jump graphic novel, 2004)
"The room of spirit and time. Cell has fused with android #17, becoming practically invicible-- but not for long! Training in the Room of Spirit and Time, where a year passes for every day outside, Vegeta and Trunks have gone beyond the Super Saiyan, reaching a level of power even greater than second-stage Cell! Now Cell is the one who is outmatched-- but Vegeta agrees to help Cell fuse with Android #18, the last element he needs to become 'perfect', so he can have the honor of defeating the strongest being in the world!"--P. [4] of cover.